CSF SerpinA1 in Creutzfeldt–Jakob disease and frontotemporal lobar degeneration - Abu‐Rumeileh, Samir (Ann Clin Transl Neurol, 2020)
OBJECTIVE: SerpinA1 (alpha‐1 antitrypsin) is an acute inflammatory protein, which seems to play a role in neurodegeneration and neuroinflammation. In Alzheimer’s disease and synucleinopathies, SerpinA1 is overexpressed in the brain and the cerebrospinal fluid (CSF) showing abnormal patterns of its charge isoforms. To date, no comprehensive studies explored SerpinA1 CSF isoforms in Creutzfeldt–Jakob disease (CJD) and frontotemporal lobar degeneration (FTLD). METHODS: Using a capillary isoelectric focusing immunoassay, we analyzed CSF SerpinA1 isoforms in control cases (n = 31) and patients with a definite or probable diagnosis of CJD (n=77) or FTLD (n = 30), belonging to several disease subtypes. RESULTS: The overall SerpinA1 signal was significantly higher than in controls in CJD subtypes linked to abnormal prion protein (PrP(Sc)) type 1, such as sporadic CJD (sCJD) MM(V)1, and in FTLD‐TDP. Moreover, CJD linked to PrP(Sc) type 1 and FTLD‐TAU groups showed a significant relative increase of acidic and basic isoforms in comparison with controls, thereby forming two distinct SerpinA1 isoform profiles. INTERPRETATION: CJD linked to PrP(Sc) type 1 and FTLD show a differential upregulation and post‐translational modifications of CSF SerpinA1. Further studies are needed to clarify whether these findings may reflect a common, albeit disease‐specific, pathogenetic mechanism related to neurodegeneration.